S-Wave Attenuation Variation and its Impact on Ground Motion Amplitudes During 2016–2017 Central Italy Earthquake Sequence - Akinci, Aybige; Munafò, Irene; Malagnini, Luca (Frontiers in Earth Science, 2022)
A very energetic seismic sequence struck the Central Apennines, Italy, in 2016-2017, with a series of damaging earthquakes, three of them with moment magnitudes M≥5.9, and five of them with M≥5.0, occurred over a few months between August 24, 2016, and late 2017. Several studies explained the phenomenon of a cascading earthquake sequence with fluid movements that provoked the rupture of different parts of the fault segments at different times and locations (e.g., Gabrielli et al., 2022; Malagnini et al., 2022; Miller et al., 2004). In this study, we investigated the variation of crustal S-wave attenuation in terms of the frequency-dependent quality factor Q(𝑓) before and after the main events (including the Amatrice, Visso, and Norcia sub-sequences, hereafter, AVN, and periods before and after the AVN multi-mainshock sequence). The spectral characteristics of regional attenuation in the Central Apennines, as well as of the earthquake sources of the AVN sequence, are derived through regression analysis using a large set of seismograms; Q(𝑓) is modeled, together with the bilinear geometrical spreading, g(r), using a widely-used tool named Random Vibration Theory, RVT (Cartwright and Longuet-Higgins, 1956). The primary objective of this effort is to examine how the variability of crustal anelastic attenuation would impact the earthquake-induced ground motions. The latter is quantified in terms of peak ground accelerations (PGAs), peak ground velocities (PGVs), and pseudo spectral accelerations at 0.3s and 2s (PSAs). Here we show that the main events of the AVN sequence strongly affect crustal S-wave attenuation, including its frequency dependence. However, the effects of 1/Q(𝑓) fluctuations on earthquake-induced ground motions are small and have a negligible impact on the seismic hazard.